The determinants of banks’ financial performance in Malaysia / Yaasmin Farzana Abdul Karim , Sharifah Nur Ainn Syed Roslan and Nurul Diana Zaini - Abdul Karim, Yaasmin Farzana; Syed Roslan, Sharifah Nur Ainn; Zaini, Nurul Diana (Faculty of Business and Management, 2013)
Bank’s financial distress issue is one of the major contributing factors to global financial crisis. Financial distress diagnosis has been a focal point of issue in financial analysis during the past decades due to its severe effects on the operation of the bank and even on the whole economy of a country. The performance of the banks will generate a more sustainable performance and promote a greater health of country's financial performance as a whole. This study investigates the determinants of banks’ financial performance. Six local commercial banks were chosen to represent the local commercial banks in Malaysia during the period of 1990-2010. The study used E-Views software to run multiple linear regression analysis which measure the relationship between Return on Equity (ROE) and its possible determining factors namely financial distress, bank size, gross domestic product (GDP), inflation rate and interest rate. The overall results reveal that the internal factors which consist of financial distress and bank size have significant impact on banks financial performance while the external factors which consist of gross domestic product (GDP), inflation rate and interest rate did not influence the banks’ financial performance. Financial distress, bank size, interest rate and inflation rate are found to have a negative relationship with the banks’ financial performance whereas gross domestic product (GDP) has a positive relationship with the banks’ financial performance.